(untitled) (Balneo and PRM Research Journal, 2024)
The main objective of the research consists in providing evidence that a long-term rehabilitation protocol is favorable for the patient. In adult brachial plexus (BP) palsies, after several surgical attempts, the lack of results in the upper limb’s functionality leads to less compliance to rehabilitation therapy. The upper limb’s functionality of 22 patients with posttraumatic operated chronic BP paresis (either on the right or left, regardless the dominant limb) was assessed retrospectively. The patients were evaluated regarding MRC scaling, dynamometric tests and electroneuromyographic examination. All patients have gone through at least one rehabilitation interval (10 days) after an initial evaluation, and were evaluated again, by same methods, at a second session, at least 6 months later, but no more than one year.. Mild and inconstant improvements were obtained in a total of 9 patients, especially in better dynamometric results and improved amplitudes of motor and sensory action potentials. The electrodiagnosis correlates with dynamometric parameters (muscle strength) and slight amelioration of the motor deficit. Given the small sample size as a limitation, as well as no standardized therapeutic protocol, it should be noted that the 9 patients were the only ones who either attended more than one interval or did more procedures as frequency in time (more often meaning 3 times weekly for 6 months, in 6 patients). Although the most frequent procedures were neuromuscular electrical stimulation (NMES) and proprioceptive neuromuscular facilitation (PNF), the results suggest that regardless of the techniques, the more active patients had better results. Proving the need for long-term rehabilitation, even contrary to the less visible results, can be the trigger point for future research and therapy strategies, as the results suggest central mechanisms involved, adding the cortical ongoing plasticity into the equation.